Connecting the Onsala telescope cluster using local interferometry - Malmnäs, Victor (My University, 2019)
The transition from legacy S/X geodetic VLBI systems to dedicated broadband receivers represented by the VGOS system require a period of operational overlap between the new and the old systems. In order to do so, local-tie measurements between the co-located telescopes at OSO and other sites needs to be performed to place the telescopes in the same reference frame. A working methodology and performance analysis of such measurements has been performed at the Onsala Space Observatory, and show promising results for future work, both locally and globally. With these results, transition to a fully operational VGOS system will be made possible.
Keywords: VLBI, VGOS, local tie-vectors, correlation, geodesy.